Do first rate scientists work at first rate organizations? - Bo, Yang; Ronald, Rousseau; Huang, Shuiqing; Yan, Sulan; Bo, Yang; Rousseau, Ronald; Huang, Shuiqing; Yan, Sulan (Malaysian Journal of Library and Information Science, 2017)
Yang, B., Rousseau, R., Huang, S., & Yan, S. (2015). Do first rate scientists work at first rate organizations?. Malaysian Journal of Library & Information Science, Vol.20, no. 1: 47-60. In this article we study the relation between first rate scientists and first rate organizations. These notions are operationalized by counting citations (whole counts in the Web of Science) for articles published during the period 2008 to 2011. Care has been taken to obtain clean data by careful institutional name disambiguation. It is found that, especially for large fields, more than 80% of top scientists work at top organizations. This is less the case for smaller fields such as mathematics and computer science. Our research confirms the skewness (elitism) of science, also for the relation between first rate scientists and the organizations to which they belong. We find, moreover, that top institutions have relatively more excellent scientists and relatively fewer researchers with poor performance than the average level of all institutions in a field.